Rubidium Fluoride Modified SnO2 for Planar n‐i‐p Perovskite Solar Cells. (17th February 2021) - Zhuang, Jing; Mao, Peng; Luan, Yigang; Chen, Ningli; Cao, Xiaofei; Niu, Guosheng; Jia, Feifei; Wang, Fuyi; Cao, Shaokui; Wang, Jizheng
Abstract: Regulating the electron transport layer (ETL) has been an effective way to promote the power conversion efficiency (PCE) of perovskite solar cells (PSCs) as well as suppress their hysteresis. Herein, the SnO2 ETL using a cost‐effective modification material rubidium fluoride (RbF) is modified in two methods: 1) adding RbF into SnO2 colloidal dispersion, F and Sn have a strong interaction, confirmed via X‐ray photoelectron spectra and density functional theory results, contributing to the improved electron mobility of SnO2 ; 2) depositing RbF at the SnO2 /perovskite interface, Rb + cations actively escape into the interstitial sites of the perovskite lattice to inhibit ions migration and reduce non‐radiative recombination, which dedicates to the improved open‐circuit voltage ( V oc ) for the PSCs with suppressed hysteresis. In addition, double‐sided passivated PSCs, RbF on the SnO2 surface, and p‐methoxyphenethylammonium iodide on the perovskite surface, produces an outstanding PCE of 23.38% with a V oc of 1.213 V, corresponding to an extremely small V oc deficit of 0.347 V. Abstract : The strong interaction between F and Sn changes the electron cloud density around Sn atoms by introducing RbF into SnO2 colloidal dispersion, contributing to the improved electron mobility of SnO2 . While spin‐coating RbF onto the SnO2 surface, the Rb + cations escape into the bulk perovskite, which inhibits ion migration and decreases the trap density.